2001
DOI: 10.1212/wnl.56.8.1052
|View full text |Cite
|
Sign up to set email alerts
|

Retest effects and cognitive decline in longitudinal follow-up of patients with early HD

Abstract: Many attention and executive tasks adequately assess the progression of the disease at an early stage. For other functions, the overlapping of retest effects and disease progression may confuse the results. High interindividual and intraindividual variability seem to be hallmarks of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
2
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 44 publications
9
82
2
1
Order By: Relevance
“…A quantitative analysis of the total number of correctly produced words showed that the patients score deteriorated over time on both letter and category fluency tasks and they also produced more repetitions. This finding is consistent with the role of the frontal lobe in tests of verbal fluency [2,9,10,17] and provides further evidence that longitudinal deterioration within HD individuals occurs, even though this is not evident from studies utilising cross-sectional paradigms [5,6].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A quantitative analysis of the total number of correctly produced words showed that the patients score deteriorated over time on both letter and category fluency tasks and they also produced more repetitions. This finding is consistent with the role of the frontal lobe in tests of verbal fluency [2,9,10,17] and provides further evidence that longitudinal deterioration within HD individuals occurs, even though this is not evident from studies utilising cross-sectional paradigms [5,6].…”
Section: Discussionsupporting
confidence: 81%
“…The effect sizes for the mean of patients' regression scores for each measure was then tested for significance with α at 0.05 (two-tailed). As patients' successive performances over time was of interest, a healthy control group was not used [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive tests were part of a comprehensive battery which has been detailed previously [16] . Cognitive tests were selected with respect to their reliability.…”
Section: Neuropsychological and Motor Assessmentmentioning
confidence: 99%
“…Although there is a rich cross-sectional literature of the functional pathology in Huntington's disease 62,63 and the unified Huntington's disease rating scale (UHDRS) provides a useful index of the stage of the disease, 64 until recently there has been very little careful analysis of the consistency of disease progression or determination of the most reliable tests in cognitive, motor, or psychiatric domains that can be used repeatedly to characterize this. As a result of the need for better assessment tools for transplantation studies, there have now been a number of detailed longitudinal studies published, 65,66 alongside the development of a core assessment protocol to allow comparison of small numbers of patients in multiple centers under standardized conditions. 67 In addition, both experimental and clinical studies have been employed to determine the efficacy and sensitivity of alternative imaging modalities to evaluate not only the extent of neurodegeneration in the disease, but also the survival of functional graft tissues in the host striatum.…”
Section: Preclinical Studiesmentioning
confidence: 99%